Criminal Policy of Netherlands and U.S.A on Decriminalization of Soft Drugs: justifications for decriminalization of soft dugs - Ehsanpour , Seyed Reza (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Soft drugs are those drugs that are very weak in terms of addiction and the effects are highly treatable. The challenging issue regarding this type of drug is the decriminalization of its use. The criminal policy of some countries such as the Netherlands agrees with the decriminalization and the criminal policy of many others such as the United States of America is against it. Materials and Methods: To review the reasons and justifications of each of parties for and against soft drug decriminalization, ideas of lawyers and scientific studies in the Netherland and the United States have been considered, and criminal poly makers’ ideas will be reviewed. Ethical Considerations: Honesty in the literature and citation analysis and reporting were considered. Findings To justify soft drug criminalization, two classifications of legal and health reasons and justifications can be cited. Legally, it has been stated that drug issue is a problem related to the health and treatment domain, and criminal legal intervention in this area must be considered just as the last weapon. In addition, Penologically, punishing soft drug users is unnecessary, ineffective, without favor, and unnecessary. Regarding health, it has been stated that not only using some soft drugs such as cannabis is not the reason for being sick, but also it has an effective role in treating incurable diseases such as multiple sclerosis, AIDS, hepatitis, chronic pain, and …. Conclusion: Decriminalization of soft drugs has a theoretical and practical background in countries such as the Netherlands and the United States. Soft drugs like cannabis not only have a lower degree of addictive rate rather than Hard drugs like heroin, but also it has some therapeutic benefits. Legally, the decriminalization of soft drugs has roots in human rights, penology, and criminological justifications. *Corresponding Author: Seyed Reza Ehsanpour; Email: ehssanpour@shahed.ac.ir; ORCID: https://orcid.org/0000-0001-9135-3968 Please cite this article as: Ehsanpour SR. Criminal Policy of Netherlands and U.S.A on Decriminalization of Soft Drugs. Bioeth Health Law J. 2021; 1: 1-0 (e11). http://doi.org/10.22037/bhl.v1i1.38155